Damsel, wonder, object: gender expectation and performance in superhero comics - Willis, Joseph J. (2016)
With iconic characters like Superman, Batman, Spider-Man, and Iron Man representing the wider culture’s understanding of comics, popular perceptions of the medium are that comics are a male-centric medium focused on male experience and readers. As the medium and the dominant superhero genre has gained attention, focus and research has been placed on the medium and how these narratives deal with representation. With the perception and stereotypes of comic readers and comic narratives as predominantly male, the question of female representation, especially within the dominant superhero genre, is a topic that has garnered attention. In my thesis, I look at the history, sources, and perpetuation of gendered performances within superhero comics. By looking at the field of comics, the perceived dominant reading position, and the constrained meaning of texts, I show that the act of creating, reading, and talking about comics are parts of a logonomic system. This system functions to deliver an expected and constrained representation and meaning about female characters and female experience. In superhero comics, female characters are constrained to performances of the monster or angel. Through the way their powers, costumes, and identities are narratively constructed, female characters are forced to be either submissive and objectified angels who conform to patriarchal power structures, or dangerous and monstrous women who need to be punished and normalized. Superhero comics work to interpolate the perceived dominant reading position, deliver pleasure, assuages fear, and transmits an expected meaning of male/female relationships and performances.